Comparison of informal caregiver and named nurse assessment of symptoms in elderly patients dying in hospital using the palliative outcome scale. Issue 2 (12th January 2016) - Dawber, Rebecca; Armour, Kathy; Ferry, Peter; Mukherjee, Bhaskar; Carter, Christopher; Meystre, Chantal
Abstract : Objectives: A prospective study of symptom assessments made by a healthcare professional (HCP; named nurse) and an informal caregiver (ICG) compared with that of the patient with a terminal diagnosis. To look at the validity of HCP and ICG as proxies, which symptoms they can reliably assess, and to determine who is the better proxy between HCP and ICG. Methods: A total of 50 triads of patient (>65 years) in the terminal phase, ICG and named nurse on medical wards of an acute general hospital. Assessments were made using the patient and caregiver versions of the palliative outcome scale (POS), all taken within a 24 h period. Agreement between patient-rated, ICG-rated and HCP-rated POS and POS for symptoms (POS-S) was measured using weighted-κ statistics. Demographic and clinical data on each group of participants were collected. Results: ICG assessments have higher agreement with those of the patient than HCP. Better agreement in both groups was found for physical symptoms, and best agreement was for pain. The worst agreements were for psychological symptoms, such as anxiety and depression, and for satisfaction with information given. Psychological symptoms are overestimated by both ICG and HCP. Conclusions: ICGs are more reliable proxies than HCPs. A trend for overestimation of symptoms was found in both groups which may lead to undervaluation of the quality of life by proxy and overtreatment of symptoms. This highlights the need to always use the patient report when possible, and to be aware of the potential flaws in proxy assessment. Reasons for overestimation by proxies deserve further research.